Pengaruh Lingkungan Kerja dan Job Burnout Terhadap Produktivitas Kerja Karyawan pada PT. Indojaya Agrinusa Medan - Elsa Safitri Siadari; Feby Aulia Safrin (Institut Agama Islam Nasional Laa Roiba Bogor, 2024)
Work productivity is a measure of the efficiency and effectiveness of an individual in an organization to produce certain output or results using a certain amount of effort in a certain time period. Productivity can be affected by the work environment and work fatigue. This research aims to analyze the influence of the work environment and job burnout on employee work productivity at PT. Indojaya Agrinusa Medan. This research uses quantitative methods involving 72 employees as research samples. Primary data was used by distributing questionnaires directly while secondary data was obtained through literature study. The results of the research conducted show that work environment variables and job burnout have a significant effect, both partially and simultaneously (together) on employee work productivity at PT. Indojaya Agrinusa Medan. The coefficient of determination test shows that there is a close relationship between the work environment and job burnout on work productivity with an R value of 0.801.